2001
DOI: 10.1002/jgm.200
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for cystic fibrosis

Abstract: Cystic fibrosis (CF) is associated with significant morbidity and mortality, despite significant advances in conventional treatment. The field of gene therapy has progressed rapidly since the cystic fibrosis transmembrane conductance regulator (CFTR) gene was cloned. In this review we discuss current knowledge on the underlying molecular defect in CF, and the progress in gene transfer studies from the early in vitro work through to clinical trials, including the development of endpoints to assess efficacy. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 81 publications
0
33
0
1
Order By: Relevance
“…Non-viral vectors under investigation include cationic lipid GL67A, DNA nanoparticles (DNA complexed with peptides) and self-assembling polyethylenimine complexes [9,35,36]. DAVIES and ALTON [35] have reported that CFTR gene transfer can be reproducibly achieved with non-viral vectors.…”
Section: Review: Cftr Modulators In Cf N Derichsmentioning
confidence: 99%
“…Non-viral vectors under investigation include cationic lipid GL67A, DNA nanoparticles (DNA complexed with peptides) and self-assembling polyethylenimine complexes [9,35,36]. DAVIES and ALTON [35] have reported that CFTR gene transfer can be reproducibly achieved with non-viral vectors.…”
Section: Review: Cftr Modulators In Cf N Derichsmentioning
confidence: 99%
“…1,2 The disease is characterized by the presence of thick secretions in the respiratory, gastrointestinal and reproductive tracts. 3 Much of the morbidity and mortality in CF patients result from pulmonary exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, we proposed (1) to examine whether gene transfer by lipoplexes was influenced by CF mucus components, (2) to explain the basis for the change in gene transfection activity, and (3) to determine whether lipoplexes that had been 'coated' with polyethylene glycol (pEG) were more resistant to CF mucus components than 'uncoated' lipoplexes.…”
Section: Introductionmentioning
confidence: 99%
“…gene delivery ͉ green fluorescent protein ͉ intracellular trafficking G ene therapy is becoming an important strategy in the treatment of various diseases such as cancer (1)(2)(3), AIDS (3)(4)(5), and cystic fibrosis (6,7). Viral vectors, the current favorites for intracellular DNA delivery, suffer from immunogenicity, nonspecificity, and inherent risks of complications such as the interference with the activity of tissue-specific promoters (8)(9)(10).…”
mentioning
confidence: 99%